Integration of Ibnu Miskawaih's Character Education and Albert Bandura's Social Learning Theory - Khairul Sya'ad, Mizani; Al-Asyhar, Thobib (Universitas Negeri Jakarta, 2025)
Background Ibnu Miskawayh's approach emphasizes the importance of noble character through the methods of role modeling, habituation, and advice, while Albert Bandura's social learning theory offers insights into children's behavioral learning. Purpose This study aims to examine the analysis of the integration of Ibn Miskawayh's character education and Albert Bandura's social cognitive learning theory in shaping children's character. Design/method/approach This research employs a qualitative method with a literature study approach, analyzing literature related to character education from the perspectives of Islam and psychology. Results The findings indicate that integrating these two approaches can create a holistic character education model encompassing moral, spiritual, and psychological aspects. The implementation of this approach is expected to strengthen children's character development comprehensively, making it relevant to the moral and ethical challenges in the era of globalization and technology. Contribution/value The study's findings contribute significantly to the development of a more effective character education curriculum and can serve as a reference for educators and policymakers in designing character education programs in schools.